A possible Link between the Jemdet Nasr and the Umm an-Nar Graves of Oman - Frifelt, Karen (The Journal of Oman Studies, 1975)
During the winter of 1972/73 a Danish archaeological team with the permission and generous support of the Oman government carried out investigations and excavations along the Wadi Jizzi/Suq connecting the Buraimi oasis across the Hajar range with Sohar on the Gulf of Oman coast. Further investigations were undertaken in the Ibri area well over 100 km south east of Buraimi and linked to this by an age-old caravan route along the Western foot of the Hajar range.